Facile synthesis of perovskite-type NdNiO3 nanoparticles for an effective electrochemical non-enzymatic glucose biosensor. (7th September 2017) - Sivakumar, Mani; Pandi, Karuppiah; Chen, Shen-Ming; Cheng, Yi-Hui; Sakthivel, Mani
Abstract : The detailed facile synthesis and material characterizations of NdNiO3 nanoparticles for a non-enzymatic glucose sensor application were discussed briefly in this paper. Abstract : The detailed facile synthesis and material characterizations of NdNiO3 nanoparticles for a non-enzymatic glucose sensor application were discussed briefly in this paper. The NdNiO3 nanoparticles that were prepared by facile synthesis show unique properties with excellent electrochemical performance and exhibit a low detection limit, as low as 0.3 μM, with an ultra-high sensitivity of 1105.1 μA mM −1 cm −2 . They were commercially suitable for real-time application in a non-enzymatic glucose sensor.